Clusterin and Its Role in Insulin Resistance and the Cardiometabolic Syndrome - Wittwer, Jennifer; Bradley, David (Frontiers in Immunology, 2021)
The cardiometabolic syndrome involves a clustering of metabolic and cardiovascular factors which increase the risk of patients developing both Type 2 Diabetes Mellitus and cardio/cerebrovascular disease. Although the mechanistic underpinnings of this link remain uncertain, key factors include insulin resistance, excess visceral adiposity, atherogenic dyslipidemia and endothelial dysfunction. Of these, a state of resistance to insulin action in overweight/obese patients appears to be central to the pathophysiologic process. Given the increasing prevalence of obesity-related Type 2 Diabetes, coupled with the fact that cardiovascular disease is the number one cause of mortality in this patient population, a more thorough understanding of the cardiometabolic syndrome and potential options to mitigate its risk is imperative. Inherent in the pathogenesis of insulin resistance is an underlying state of chronic inflammation, at least partly in response to excess adiposity. Within obese adipose tissue, an immunomodulatory shift occurs, involving a preponderance of pro-inflammatory immune cells and cytokines/adipokines, along with antigen presentation by adipocytes. Therefore, various adipokines differentially expressed by obese adipocytes may have a significant effect on cardiometabolism. Clusterin is a molecular chaperone that is widely produced by many tissues throughout the body, but is also preferentially overexpressed by obese compared lean adipocytes and relates strongly to multiple components of the cardiometabolic syndrome. Herein, we summarize the known and potential roles of circulating and adipocyte-specific clusterin in cardiometabolism and discuss potential further investigations to determine if clusterin is a viable target to attenuate both metabolic and cardiovascular disease.